A novel technique- subendometrial autologous platelet rich plasma injection in patients with unresponsive thin endometrium undergoing frozen-thawed embryo transfer: a prospective cohort study - Yigit Cakiroglu; Yusuf Aytac Tohma; Aysen Yuceturk; Ozge Karaosmanoglu; Ilke Ozer Aslan; Sule Yildirim Kopuk; Zeynep Ece Utkan Korun; Caglar Yazicioglu; Hulusi Bulent Zeyneloglu; Bulent Tiras (BMC Pregnancy and Childbirth)
Abstract Background The purpose of this study was to investigate the effects of subendometrial PRP injection on endometrial thickness and pregnancy outcomes in patients with a history of unresponsive thin endometrium undergoing frozen-thawed embryo transfer (FET). Methods This prospective cohort study was conducted at Acibadem Mehmet Ali Aydinlar University-Istanbul, Turkey. Women with a history of suboptimal endometrial proliferation (< 7 mm) were offered to participate in the study. Group 1 consisted of 100 individuals who consented to subendometrial PRP injection, while Group 2 consisted of 100 individuals who did not accept PRP injection. Within ten days of the menstrual cycle ending, autologous PRP was produced by centrifuging peripheral blood and administered transvaginally into the subendometrial region under ultrasound monitoring. After the PRP procedure, 14 days of oral estradiol supplementation were started as part of the hormonal treatment on the 2-4th day of the second menstrual cycle. Women determined to have adequate endometrial thickness following the initiation were scheduled for embryo transfers. Embryo transfer was scheduled for women who were found to have adequate endometrial thickness after the initiation of progesterone. Pregnancy (positive serum hCG) and livebirth rates were followed. Results A total of 200 women (age 36.4 ± 5.8) were included in the study. Endometrial thickness increased after PRP therapy as compared to the control group (7.7 ± 1.9 mm vs. 6.1 ± 1.2 mm; p < 0.01). Three women (3.0%) in the PRP group conceived spontaneously, whereas 97 women (97.0%) attempted FET; no spontaneous pregnancies occurred in the control group. Compared to 75/100 (75% of the total) in the control group, 33/97 women (34.0%) in the PRP group were unable to undertake ET because of persistently unresponsive thin endometrium or fluid in the endometrial cavity (p < 0.001). The PRP group had a considerably higher percentage of positive serum hCG tests than the control group (25.8% vs. 9.0%; p = 0.002). Additionally, the PRP group had a higher clinical pregnancy rate (22.7% vs. 7.0%; p = 0.002). The live birth rate was significantly higher in the PRP group than the controls (17.5% vs. 2.0%; p < 0.001). Conclusions In women with a history of suboptimal endometrial development, subendometrial PRP injection was associated with improved endometrial thickness and livebirth rate. Trial registration Baskent University institutional review board and ethics committee (KA-20/23) http://www.Clinicaltrials.gov , (NCT04424160), 2020.06.15.